Preparation of Some Food From Animal Meat Proteins and Study Its Chemical and Sensory Properties - Al- Delami, O. F.; Al- Mashikhi, Shalan A.; Al- Azawi, Hannan T. (The Iraqi Journal of Veterinary Medicine, 2000)
This study was aimed to prepare ready food from some meat proteins . Two groups of protein fractions were I.E. water- soluble (sarcoplasmic proteins ) and water insoluble (myofibrial proteins) were obtained. There recipes of sarcoplasmic proteins were prepared , the first recipe contained corn starch, potato , oil, salt and spices, the second recipe contained tomato juice, naringe juice, oil, salt and spice; while the third recipe contained rice flour. naringe juice, oil, salt and spice. Chemical and sensory evaluation were carried out on these recipes . Myofibrial proteins (actin, myosin , and stroma proteins I.E. collagen and elastin) were lyophilized in order to prepare different soup recipes and study its sensory characteristics .